Unfolding alignment - How top management work to align demand and capacity: an ethnographic study of resilience in a Swedish healthcare region - Ingrid Svensson; Mia von Knorring; Heidi Hagerman; Cecilia Fagerström; Mirjam Ekstedt; Lisa Smeds Alenius (BMC, 2023)
Abstract Background Resilient healthcare organizations maintain critical functions and high-quality care under varying conditions. While previous research has focused on the activities of frontline healthcare professionals working at the "sharp end" of care, less attention has been paid to managers at the top management level. More knowledge is needed to fully understand how the managers align demand and capacity at the "blunt end" of care. Therefore, this study aimed to explore how top managers work to align demand and capacity in a healthcare region in Sweden. Methods Observations of management team meetings, interviews, and conversations were conducted with top managers responsible for healthcare in one of Sweden's 21 regions. Data collection used an ethnographic approach. Data were analyzed using qualitative reflexive thematic analysis. Results The data showed how alignment work was done through active reflection that built on past experiences and on structures built into the organization at the same time as taking future potential outcomes and consequences into account. In addition to collaborative, preventive, supportive, and contextualizing work, which was conducted in the present, a general approach permeated the organization, which enabled connecting actions, i.e., different forms of alignment work, occurring at different points in time, and connecting different types of knowledge across organizational borders and stakeholders. Conclusion This study explored how top managers work to align demand and capacity in a healthcare region in Sweden. It was shown how four categories of work; collaborative, preventive, supportive and contextualization work, together with a general approach; focusing on opportunities, building on a stable past and taking a reflective stance, constitute alignment in practice. More; the alignment work was done in the here and now, with both the past and future in mind. The ability to take action to benefit the whole is a possibility and a responsibility for top management. In the region studied, this was done by aligning demands with capacity based on past experiences and focusing on the available opportunities to connect knowledge needed within and across organizational borders.